Decolonial Reflections on Mapuche Wisdom and Sensory Thinking - Salinas, Cecilia G. (Nordlit, 2025)
Through an ethnographic study, the article contributes to the conversation on decolonial philosophy by promoting a dialogue between Indigenous experiential knowledge forms and Western philosophy as equally valid approaches to understanding the world. The analysis is based on the Mapuche people of Patagonia (Argentina and Chile) and their concepts of rakizuam (sensory thinking) and kimün (wisdom). It is argued that Indigenous onto-epistemologies should not be regarded as curiosities, but as valuable contributions to Western thought. The dominant philosophical canon would undoubtedly look different had it embraced more of the alternative perspectives that, even within Western philosophy itself, have developed understandings of the world closely related to Indigenous holistic perspectives.